2020
DOI: 10.7441/joc.2020.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Asian Model of Clusters and Cluster Policy: The Super Cluster Strategy

Abstract: Clusters are recognized as important drivers of competitiveness and economic development. There are various models of clusters development all over the world, some of which may be initiated bottom-up by private firms, as in most European countries, or top-down by public administrations. In the case of Asian clusters, many are driven by foreign direct investments (FDI), with the most notable example being China. The objective of this study is to examine the Super Cluster strategy introduced in Thailand in 2015,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
1
13
0
3
Order By: Relevance
“…World experience and domestic practice show that agricultural clusters are an effective tool for the socio-economic development of agricultural regions. The main advantages of the agrocluster making it an instrument of regional policy encompass [13][14]:…”
Section: Discussionmentioning
confidence: 99%
“…World experience and domestic practice show that agricultural clusters are an effective tool for the socio-economic development of agricultural regions. The main advantages of the agrocluster making it an instrument of regional policy encompass [13][14]:…”
Section: Discussionmentioning
confidence: 99%
“…Most authors consider the organic ("grass root") model of cluster creation by private companies a more effective one, leading to stronger results (Razminien ė et al 2021). They underline that the model of cluster initiation led by public administration usually provokes a sudden reaction with a less probable long-term existence of the newly established cluster (Kowalski 2020).…”
Section: Industrial Cluster As An Inter-organizational Networkmentioning
confidence: 99%
“…The general feature of different studies on innovation system is that they emphasize a set of interacting actors working together toward a shared goal of innovation [Lee et al, 2020]. A special form of cooperation are clusters which bring together academic institutions, research organizations or centers of excellence in specific regions, what can be observed mostly in the European Union [Kowalski, 2020]. This approach goes in line with open innovation paradigm, which states that one of the key factors of successful innovation activity is cooperation as the sources of innovation may be found not only inside, but also outside the company [Chesbrough, 2003].…”
Section: Theoretical Backgroundmentioning
confidence: 99%